Activating Connexin43 gap junctions primes adipose tissue for therapeutic intervention - Yi Zhu; Na Li; Mingyang Huang; Xi Chen; Yu A. An; Jianping Li; Shangang Zhao; Jan-Bernd Funcke; Jianhong Cao; Zhenyan He; Qingzhang Zhu; Zhuzhen Zhang; et al. (Elsevier, 2022)
Adipose tissue is a promising target for treating obesity and metabolic diseases. However, pharmacological agents usually fail to effectively engage adipocytes due to their extraordinarily large size and insufficient vascularization, especially in obese subjects. We have previously shown that during cold exposure, connexin43 (Cx43) gap junctions are induced and activated to connect neighboring adipocytes to share limited sympathetic neuronal input amongst multiple cells. We reason the same mechanism may be leveraged to improve the efficacy of various pharmacological agents that target adipose tissue. Using an adipose tissue-specific Cx43 overexpression mouse model, we demonstrate effectiveness in connecting adipocytes to augment metabolic efficacy of the β3-adrenergic receptor agonist Mirabegron and FGF21. Additionally, combing those molecules with the Cx43 gap junction channel activator danegaptide shows a similar enhanced efficacy. In light of these findings, we propose a model in which connecting adipocytes via Cx43 gap junction channels primes adipose tissue to pharmacological agents designed to engage it. Thus, Cx43 gap junction activators hold great potential for combination with additional agents targeting adipose tissue.